Proglucagon-Derived Peptides Expression and Secretion in Rat Insulinoma INS-1 Cells - Acosta-Montalvo, Ana; Saponaro, Chiara; Kerr-Conte, Julie; Prehn, Jochen H. M.; Pattou, François; Bonner, Caroline (Frontiers in Cell and Developmental Biology, 2020)
Rat insulinoma INS-1 cells are widely used to study insulin secretory mechanisms. Studies have shown that a population of INS-1 cells are bi-hormonal, co-expressing insulin, and proglucagon proteins. They coined this population as immature cells since they co-secrete proglucagon-derived peptides from the same secretory vesicles similar to that of insulin. Since proglucagon encodes multiple peptides including glucagon, glucagon-like-peptide-1 (GLP-1), GLP-2, oxyntomodulin, and glicentin, their specific expression and secretion are technically challenging. In this study, we aimed to focus on glucagon expression which shares the same amino acid sequence with glicentin and proglucagon. Validation of the anti-glucagon antibody (Abcam) by Western blotting techniques revealed that the antibody detects proglucagon (≈ 20 kDa), glicentin (≈ 9 kDa), and glucagon (≈ 3 kDa) in INS-1 cells and primary islets, all of which were absent in the kidney cell line (HEK293). Using the validated anti-glucagon antibody, we showed by immunofluorescence imaging that a population of INS-1 cells co-express insulin and proglucagon-derived proteins. Furthermore, we found that chronic treatment of INS-1 cells with high-glucose decreases insulin and glucagon content, and also reduces the percentage of bi-hormonal cells. In line with insulin secretion, we found glucagon and glicentin secretion to be induced in a glucose-dependent manner. We conclude that INS-1 cells are a useful model to study glucose-stimulated insulin secretion, but not that of glucagon or glicentin. Our study suggests Western blotting technique as an important tool for researchers to study proglucagon-derived peptides expression and regulation in primary islets in response to various metabolic stimuli.